Pengaruh Motivasi dan Disiplin Kerja Terhadap Kepuasan Kerja yang Berimplikasi Pada Kinerja Karyawan di PT. Qtera Mandiri - Yolanda Yolanda; Rut Natal Uli Girsang (Fakultas Ekonomi Universitas Borobudur, 2021)
This study aims to determine the extent of the influence of work motivation and workdiscipline on job satisfaction and its implications for employee performance at PT. QteraMandiri.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 60 people. The data processing method uses the path analysismethod with the helpan SPSS version 22.0. Statistical testing used the significance test of individual parameters(t test) and simultaneous significance test (F test).The results showed that simultaneously the variables of work motivation, work disciplineand job satisfaction have a significant effect on employee performance. Partially it shows thatanalysis 1: work motivation variables have a significant effect on employee performance, andanalysis 2: work discipline variables have a significant effect on employee performance.Furthermore, in analysis 3: job satisfaction variables have a significant effect on employeeperformance.Keywords: work motivation, work discipline, job satisfaction and employee performance